Protection from Oxygen Toxicity with Endotoxin: ROLE OF THE ENDOGENOUS ANTIOXIDANT ENZYMES OF THE LUNG - Frank, L. (1980)
Endotoxin treatment of adult rats before hyperoxic exposure significantly increases their survival rate in >95% O(2) (J. Clin. Invest.61: 269, 1978). In this study, we wished to determine: (a) whether endotoxin would protect against O(2) toxicity if it were administered after the animals were already in >95% O(2) for 12-48 h; and (b) the relationship between the endogenous antioxidant enzymes of the lung and the protective effect of endotoxin treatment. Our results showed that adult rats given a single 500 μg/kg dose of endotoxin up to 36 h after the onset of O(2) exposure had significantly increased survival rates and decreased lung fluid accumulation compared to untreated animals in O(2) (P < 0.05). (Survival, 16/49 [untreated rats]; 18/20 [endotoxin at 12 h after the start of O(2) exposure]; 25/26 [endotoxin-24 h]; 15/20 [endotoxin-36 h].) Endotoxin-treated animals in O(2) showed increases in pulmonary superoxide dismutase, catalase, and glutathione peroxidase activities before the usual time of onset of measurable pulmonary edema in untreated animals in O(2). When diethyldithiocarbamate was used to block the superoxide dismutase enzyme rise in the endotoxin-treated rats in O(2), the protective action of endotoxin against pulmonary O(2) toxicity was nullified. In endotoxin-treated, O(2)-exposed mice, there were no lung antioxidant enzyme increases, and no protective effect from O(2) toxicity was achieved. We conclude that, in the rat, a single dose of endotoxin given even 36 h after the onset of hyperoxic exposure results in marked protection against O(2)-induced lung damage; and the increased lung antioxidant enzyme activity in the endotoxin-treated rats appears to be an essential component of this protective action.